STRES KERJA, KEPUASAN KERJA, DAN IKLIM ORGANISASI TERHADAP TURNOVER INTENTION PADA DIVISI KEUANGAN PT XYZ - GENUINE EKA PRASETIYO; SETIA TJAHYANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research is to examine the effect of human resource management practice such as work stres, job satisfaction and organization climate on turnover intention of Finance Division PT. Mayora Indah Tbk Head Office Jakarta. The sampling in this research was purposive sampling, in which only 89 collected data that accordance with the criteria. Data for this study comes from primary source garnered by distributing LikertScale questionnaires. The data is then analyzed with SPSS version 23 program using Simple Linear Regressions and Multiple Regressions Analysis. The result on this research is work stres and organization climate have a significant influence to turnover intention individually. Job satisfaction not have a significant influence to turnover intention.